Fluoride in Mozambique: retrospective study - Marta Artemísia Abel Mapengo DOMINGOS; Sílvia Helena de Carvalho SALES PERES (RGO: Revista Gaúcha de Odontologia, 2023)
ABSTRACT Objective: The study aims to analyse the fluoride concentration in the water supply of the capital of each province of Mozambique, 2019 and compare with previous data 1978 and 2008. Methods: The water supply in cities of Mozambique were analysed in 1978, 2008 and 2019 and water from Tete’s River in 1978 and 2019. The fluoride concentration of the water samples was determined in duplicate, using the ion-sensitive electrode (Orion 9609), coupled to a potentiometer (Procyon, model 720), adopting a significance level of 5%. Results: The average fluoride concentration found in the years 1978, 2008 and 2019 was 0.31, 0.33 and 0.14 mg F/L, respectively. The fluoride concentrations collected from household taps in 1978, 2008 and 2019 were: Cabo Delgado/Pemba (0.62, 0.28 and 0.07 mg F/L), Niassa/Lichinga (0.18, 0.98 and 0.07 mg F/L), Nampula/Nampula (0.18, 0.01 and 0.06 mg F/L), Zambézia/Quelimane (0.81, 0.37 and 0.15 mg F/L), Tete/Tete (1.00, 0.97 and 0 .46 mg F/L), Sofala/Beira (0.00, 0.01 and 0.10mg F/L), Manica/Chimoio (0.04, 0.01 and 0.07 mg F/L), Inhambane/Inhambane (0.00, 0.05 and 0.19 mg F/L), Gaza/Xai-Xai (0.01, 0.06 and 0.06 mg F/L) and Maputo (0.23, 0.36 and 0.23 mg F/L), respectively. In the waters of the Zambeze River was 5.5 mg F/L in 1978 and 0.12 mg F/L in 2019. There was no significant change between the fluoride concentrations in the water collected from the taps during the periods studied (p=0.83), however there was a significant difference in the water collected from the river (p<0.05). Conclusion: Tete’ River showed a significant reduction in fluoride concentration, and in the piped water collected in all municipalities, the fluoride content was below optimum.